Antioxidant Activity and HR-LCMS Analysis of Phytochemicals Present in the Methanolic Extract of the Rhizomes of Paris Polyphylla (Satuwa) - Magar, Paurakh; Pokhrel, Galaxy; Silwal, Sachin; Thapa, Sabi; Mahato, Ajaya; Adhikara, Bishisha; Bagale, Shiva; Shrestha, Pabitra; Bhattarai, Bodhbabu; Pokhrel, Ganga Raj (Api Journal of Science, 2024)
Antioxidant activity and the complete High-Resolution Liquid Chromatography Mass Spectrometry (HR-LCMS) metabolomic profiling of the rhizomes of Paris polyphylla is still unknown. This study mainly focused on the analysis of the phytochemicals present in the methanolic extract of the rhizomes of P. polyphylla. The roots of Paris polyphylla is used in traditional medicine as counteragent for snake bite, remedy for insect poison, relieve for wounds, sore throat etc. Like other medicinal plants, root of Paris polyphylla contains numerous potential bioactive compounds. Such bioactive compounds have significant antioxidant activity. Quantative measurement of total Flavonoids, phenolics and antoxidants were carried using spectrometric technique based on quercetin, gallic acid and ascorbic acid as the standards. The total flavonoids content is calculated as 38.430.27mg QE/g dry weights. Moreover the total phenolic constitutes 41.470.53 mg GAE/g dw and the total antioxidant comprises 20.690.97 mg Ascorbic acid equivalent/g dw. HR-LCMS analysis conducted in both positive and negative ESI modes revealed the presence of 128 distinct molecules. Root of P. Polyphylla possesses valuable antioxidant properties for dietary and medicinal use.